Long-term benefit of enzyme replacement therapy in Pompe disease: A 5-year prospective study. (5th December 2017) - Kuperus, Esther; Kruijshaar, Michelle E.; Wens, Stephan C.A.; de Vries, Juna M.; Favejee, Marein M.; van der Meijden, Jan C.; Rizopoulos, Dimitris; Brusse, Esther; van Doorn, Pieter A.; van der Ploeg, Ans T.; van der Beek, Nadine A.M.E.
Abstract : Objective: To determine the effect of enzyme replacement therapy (ERT) after 5 years and to identify predictors for a favorable response because few data are available on the long-term efficacy of ERT in Pompe disease. Methods: We included 102 adult patients with Pompe disease in a nationwide, prospective cohort study. We assessed muscle strength (manual muscle testing with Medical Research Council [MRC] grading, handheld dynamometry [HHD]), muscle function (6-minute walk test, Quick Motor Function Test), daily life activities (Rasch-Built Pompe-Specific Activity [R-PAct] Scale), and pulmonary function (forced vital capacity [FVC] in upright and supine positions, maximum inspiratory and expiratory pressures) at 3- to 6-month intervals before and after the start of ERT. Data were analyzed with linear mixed-effects models for repeated measurements. Results: Median follow-up duration was 6.1 years (range 0.4–7.9 years), of which 5.0 years (range 0.2–7.3 years) were during ERT. Treated patients had better muscle strength (MRC sum score +6.6 percentage points [pp]; HHD sum score +9.6 pp, both p < 0.0001), activity levels (R-PAct +10.8 pp, p < 0.002), and pulmonary function (FVC upright +7.3 pp, FVC supine +7.6 pp, both p < 0.0003) than expected for their untreated disease course. Walking distance improved (416 vs 376 m at baseline, p = 0.03). The largest increase was seen during the first 2 to 3 years of treatment. Response to treatment was similar between groups regardless of sex, age, or disease duration. Conclusions: Long-term ERT positively affects muscle strength, pulmonary function, and daily life activities in adult patients with Pompe disease, with a peak effect at ≈2 to 3 years of treatment. Classification of evidence: This study provides Class IV evidence that for patients with Pompe disease, long-term ERT positively affects muscle strength, pulmonary function, and daily life activities.